Decision to return to sport after anterior cruciate ligament reconstruction, Part I: A qualitative investigation of psychosocial factors - Burland, J. P.; Toonstra, J.; Werner, J. L.; Mattacola, C. G.; Howell, D. M.; Howard, J. S. (Journal of Athletic Training, 2018)
Context: Return-to-sport criteria after anterior cruciate ligament (ACL) injury are often based on "satisfactory" functional and patient-reported outcomes. However, an individual's decision to return to sport is likely multifactorial; psychological and physical readiness to return may not be synonymous.